2018
DOI: 10.1097/mej.0000000000000461
|View full text |Cite
|
Sign up to set email alerts
|

The superiority of the two-thumb over the two-finger technique for single-rescuer infant cardiopulmonary resuscitation

Abstract: The TTT produced deeper CCD compared with that of the TFT-R23 because the finger strength of the TTT was significantly higher than that of the TFT-R23.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…Systematic reviews suggest that the 2-thumbencircling hands technique may improve CPR quality when compared with 2-finger compressions, particularly for depth. 42,43 However, recent manikin studies suggest that the 2-thumb-encircling hands technique may be associated with lower chest compression fractions (percent of cardiac arrest time that chest compression are provided) 44 and incomplete chest recoil, 45,46 especially when performed by single rescuers. See Figure 3 for the 2-thumb-encircling hands technique.…”
Section: The Optimum Compression-to-ventilation Ratio Ismentioning
confidence: 99%
“…Systematic reviews suggest that the 2-thumbencircling hands technique may improve CPR quality when compared with 2-finger compressions, particularly for depth. 42,43 However, recent manikin studies suggest that the 2-thumb-encircling hands technique may be associated with lower chest compression fractions (percent of cardiac arrest time that chest compression are provided) 44 and incomplete chest recoil, 45,46 especially when performed by single rescuers. See Figure 3 for the 2-thumb-encircling hands technique.…”
Section: The Optimum Compression-to-ventilation Ratio Ismentioning
confidence: 99%
“…The results of the present study showed that compared to "at least one-third the anteriorposterior diameter of the chest", the term "approximately 4 cm" could significantly limit the CCD. The CCD has been reported to be usually higher with TT when compared to TFT [12,[31][32][33][34]. However, in this study, ACD and the proportion of cases wherein the adequate depth was achieved were significantly different between the groups for both TT and TFT (Fig 2).…”
Section: Plos Onementioning
confidence: 48%
“…The ACD for TFT with the index and middle fingers of the right hand was 41.6 ± 1.1 mm and the ACD for TT was 43.1 ± 0.9 mm in a previous study [12]. We hypothesized that the ACD with a target CCD of "approximately 4 cm" would be lower than that with a target CCD of "at least one-third the anterior-posterior diameter of the chest" by as much as the standard deviation (1.1 mm for TFT and 0.9 mm for TT).…”
Section: Sample Size Calculationmentioning
confidence: 68%
See 1 more Smart Citation
“…The mean (SD) chest com-pression pressure of OHCC was reported to be 75.1 (12.02) mmHg (compared with the two-handed chest compression technique: 86.6 [13.68] mmHg) [5]. However, the mean (SD) chest compression power of 2f was reported to be 13.7 (5.1) kg with the right index-middle finger and 12.6 (4.6) kg with the left index-middle finger (compared with 2T: 23.8 [10.1] kg) [6]. The diversity of 1H might conceal the difference in CCD between 2T and 2f.…”
mentioning
confidence: 99%